Karyotypes of Four Species and One Form of the Genus Semisulcospira (Neotaenioglossa: Pleuroceridae) in Lake Biwa - Takami, Akihiro (Venus (Journal of the Malacological Society of Japan), 2022)
The karyotypes of four species and one form of the genus Semisulcospira in Lake Biwa, Japan were examined. The observed diploid chromosome number of each taxon was as follows: Semisulcospira niponica and S. niponica form biwae, 2n=26 (20M+4SM+2ST); S. decipiens, 2n=26 (22M+2SM+2ST); S. takeshimensis, 2n=26 (18M+6SM+2ST); S. shiraishiensis, 2n=28 (18M+8SM+2T).